R430: A potent inhibitor of DNA and RNA viruses. Issue 1 (December 2018) - D'Aiuto, Leonardo; McNulty, James; Hartline, Caroll; Demers, Matthew; Kalkeri, Raj; Wood, Joel; McClain, Lora; Chattopadhyay, Ansuman; Zhi, Yun; Naciri, Jennifer; Smith, Adam; Yolken, Robert; et al.
Abstract Acyclovir (ACV) is an effective antiviral agent for treating lytic Herpes Simplex virus, type 1 (HSV-1) infections, and it has dramatically reduced the mortality rate of herpes simplex encephalitis. However, HSV-1 resistance to ACV and its derivatives is being increasingly documented, particularly among immunocompromised individuals. The burgeoning drug resistance compels the search for a new generation of more efficacious anti-herpetic drugs. We have previously shown that trans-dihydrolycoricidine (R430), a lycorane-type alkaloid derivative, effectively inhibits HSV-1 infections in cultured cells. We now report that R430 also inhibits ACV-resistant HSV-1 strains, accompanied by global inhibition of viral gene transcription and enrichment of H3K27me3 methylation on viral gene promoters. Furthermore, we demonstrate that R430 prevents HSV-1 reactivation from latency in anex vivo rodent model. Finally, among a panel of DNA viruses and RNA viruses, R430 inhibited Zika virus with high therapeutic index. Its therapeutic index is comparable to standard antiviral drugs, though it has greater toxicity in non-neuronal cells than in neuronal cells. Synthesis of additional derivatives could enable more efficacious antivirals and the identification of active pharmacophores.